Family Support On Compliance With Taking Hypertension Medication In The Elderly At Tanjung Ria Public Health Center Jayapura City - Kurniawan Edi Priyanto; Sutrisno; Berneti Bura Loko (Journal for Research in Public Health, 2026)
Lack of family support can cause elderly people to be non-compliant in taking hypertension medication, increasing the risk of complications. Emotional support and regular supervision are crucial for elderly people to feel cared for. Families play a role in reminding them of medication schedules and encouraging adherence. With proper attention, the risk of hypertension can be controlled more optimally. This study aims to determine the relationship between family support and adherence to hypertension medication in elderly people at the Tanjung Ria Community Health Center in Jayapura City. This research method used a correlational analytical design with a population of 125 people and a sample of 125 people using a total sampling technique. The instrument used a questionnaire with Spearman rank test analysis. The results of this study showed that family support showed that the majority had good support (65 people (52.0%). Medication adherence showed that the majority was compliant (70 people (56.0%). There was a relationship between family support and adherence to hypertension medication in elderly people at the Tanjung Ria Community Health Center in Jayapura City with a p-value of 0.000 (0.05). Good family support plays an important role in increasing elderly adherence to hypertension medication. The higher the support provided, the more likely the elderly are to follow treatment with discipline. Families can help by reminding them of medication schedules and providing motivation. This can reduce the risk of hypertension complications. Furthermore, good communication within the family can increase the comfort of older adults undergoing treatment. The family's attention and active involvement will encourage older adults to be more aware of the importance of maintaining their health.